Prevalence and Associated Factors of Urinary Incontinence among Elderly in Pekanbaru, Indonesia - Sari, Wulan (UI Scholars Hub, 2021)
Background: The proportion of the elderly in Riau Province was 4.8% higher than that (4.2%) in 2011. Urinary incontinence (UI) is a common health problem among the elderly. This study aims to determine the prevalence and associated factors for UI among the elderly (≥60 years). Methods: This cross-sectional study was conducted in 20 public health centers in Pekanbaru City in 2018. A total of 351 elderly meeting the inclusion criteria were enrolled. Gender, age, education, occupation, marital status, obesity, depression, cognitive impairment, smoking status, history of chronic cough, and history of lower abdominal surgery served as the independent variables and UI as the dependent variable. Data were collected through interviews facilitated by staff trained by the research team. Data were analyzed using multiple logistic regression with a predictive factor model to assess the relationship between the independent and dependent variables. Results: The prevalence of UI was 6%, and the associated factors were chronic cough (prevalence odds ratio = 17.661; 95% CI: 6.380–48.884). Gender, age, education, and lower abdominal surgery were the confounding factors. Conclusions: Health workers at the public health center of Pekanbaru should educate the community and the elderly about the potential causes, prevention, and treatment of UI.